Development of A Surveillance And Remote Control System Based On ESP-Now For The ATSV Prototype (Autonomous Tourism Surface Vessel) - Fikri Firmansyah; Diptya Widayaka, Parama (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2023)
Indonesia, as an archipelagic country, has great potential in the marine tourism sector. One of the efforts to develop maritime technology is through the National Unmanned Fast Boat Contest (KKCTBN), which aims to encourage innovation in unmanned ship manufacturing. This research aims to design and implement a GPS surveillance system and remote steering control on the Autonomous Tourism Surface Vessel (ATSV) prototype by utilizing ESP-NOW wireless communication technology. The system uses an ESP32 microcontroller, a NEO-6M GPS sensor, and a joystick module as part of the hardware, as well as ESP-NOW as a communication protocol to overcome the limitations of internet connectivity in the ocean area. Ship position data is sent in real-time to Thingspeak servers for remote monitoring. The test results show that the system can transmit GPS data with good accuracy and control the ship's direction responsively at a distance of up to 50 meters using an external antenna. Tests also show that the system can function well in various communication conditions and is reliable in monitoring and controlling ATSV vessels in real-time. This system is expected to contribute to innovation in the maritime world, especially in the context of developing unmanned ships that compete in the KKCTBN. Keywords: Autonomous Tourism Surface Vessel (ATSV), KKCTBN, ESP-NOW, GPS surveillance, steering control, Thingspeak, ESP32, NEO-6M GPS sensor